2007
DOI: 10.1007/s11242-007-9191-7
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Relationships Among Capillary Pressure, Saturation, Interfacial Area and Relative Permeability Using Pore-Network Modeling

Abstract: To gain insight in relationships among capillary pressure, interfacial area, saturation, and relative permeability in two-phase flow in porous media, we have developed two types of pore-network models. The first one, called tube model, has only one element type, namely pore throats. The second one is a sphere-and-tube model with both pore bodies and pore throats. We have shown that the two models produce distinctly different curves for capillary pressure and relative permeability. In particular, we find that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
162
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(178 citation statements)
references
References 38 publications
9
162
2
Order By: Relevance
“…This analysis corroborates previous experimental and computational studies (e.g., Reeves and Celia 1996;Held and Celia 2001;Cheng et al 2004;Chen et al 2007;Joekar-Niasar et al 2008, 2010bPorter et al 2009). It is presented here in order to establish equilibrium P c -S w -a nw surface needed for comparison to the corresponding non-equilibrium surface.…”
Section: On the Uniqueness Of Equilibrium P C -S W -A Nw Surfacessupporting
confidence: 91%
See 1 more Smart Citation
“…This analysis corroborates previous experimental and computational studies (e.g., Reeves and Celia 1996;Held and Celia 2001;Cheng et al 2004;Chen et al 2007;Joekar-Niasar et al 2008, 2010bPorter et al 2009). It is presented here in order to establish equilibrium P c -S w -a nw surface needed for comparison to the corresponding non-equilibrium surface.…”
Section: On the Uniqueness Of Equilibrium P C -S W -A Nw Surfacessupporting
confidence: 91%
“…In another study that compares experimental and pore-network model results for glass beads experiments, a similar conclusion was reached (Joekar-Niasar et al 2010b). These results indicated that inclusion of a nw leads to the removal or significant reduction of hysteresis in P c -S w relationship (see e.g., Reeves and Celia 1996;Held and Celia 2001;Cheng et al 2004;Chen et al 2007;Joekar-Niasar et al 2008;Porter et al 2009). All these studies have a common characteristics: the analyses were conducted under equilibrium conditions in which the capillary interfaces do not move in mostly granular media.…”
Section: List Of Symbolsmentioning
confidence: 91%
“…The radii of sites were given by an uncorrelated truncated lognormal probability distribution and the radii of bonds were determined by size of the sites which are located at the two ends of each bond. This scheme was adopted from Acharya et al (2004) and used by Joekar-Niasar et al (2007). The resulting porosity is shown in Table 2.…”
Section: Generating a Consolidated Porous Medium (Sandstone Sample)mentioning
confidence: 99%
“…Pore-network models [8][9][10][11][12][13][14][15][16] are a viable tool for understanding multiphase flows at the pore scale, and they are computationally efficient. These models, however, are based upon simplified representations of the complex pore geometry [17], which restricts their predictive capability and accuracy.…”
Section: Introductionmentioning
confidence: 99%